Explaining the Nursing Students\' Lived Experience of Moral Courage in Clinical Environments - Leila Mardanian Dehkordi; Sahar Khoshkesht; Narges Hashemi; Ameneh Yaghoobzadeh (Hamadan University of Medical Sciences, 2024)
Background and Objective: Moral courage is considered a part of the requirements of the nursing profession, and its prerequisite is the training and strengthening of this characteristic during student's study period. Therefore, this study aimed to explore nursing students' lived experiences of moral courage practiced in clinical settings. Materials and Methods: The current research was conducted using hermeneutic phenomenological approach. purposeful sampling method was performed among the 7th and 8th semester nursing students who had completed their theoretical courses. Data collection continued using semi-structured interviews until data saturation, and finally 10 individuals participated in this study, and data analysis was done based on Dickelmann approach. Results: The obtained results indicated two main themes, including moral conscience (decisiveness in correcting actions and moral governance) and ethical strategy development (personal commitment and moral evolusion). Conclusion: The findings of this research showed that students with moral courage have moral conscience, including determination to correct actions and moral governance, and this characteristic enhances professional ethics. Considering that the main mission of nursing education is to train capable and competent nurses who have the necessary knowledge and skills to provide quality nursing care, maintain and improve the health of society, educational systems can use the results of this study to evaluate their educational programs and correct their defects.